(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Herdananta BY, Charsyah C, Putra CDH, Mumpuni CHY, Nofitasari H, Setyawan AD. 2025. Diversity of insect pollinators in the buffer zone of Mount Merapi National Park, Indonesia. Asian J Agric 9: 149-159. Pollinating insects have a significant impact on plant reproduction on land, accounting for almost 90% of their function. Both the environment and vegetation influence the presence of pollinating insects. This study aims to analyze the diversity of pollinating insects in several habitat types in the buffer zone of Mount Merapi National Park (MMNP), Tegalmulyo and Sidorejo Villages, Kemalang, Klaten, Indonesia. This research was conducted in March 2024 by taking 3 habitat types, namely forests, agricultural fields, and shrublands, each with 4 replicates. The research method used is a roaming research purposive random sampling technique, and the sampling point was determined at the selected location based on the survey results and accompanied by direct observation. Furthermore, data analysis was carried out on the species ecological index (diversity, richness and evenness), Species Accumulation Curve (SAC) and its relationship with abiotic factors. The results of the study found pollinator insects totaling 121 individuals consisting of 55 species, 26 families, and 5 orders, namely the order Coleoptera, Diptera, Hemiptera, Hymenoptera, and Lepidoptera. There are several flowering plants infested by pollinating insects; 15 plant species were obtained and divided into 11 different families. The results of the calculation of the pollinator species diversity index were 3.731, a species richness index of 11.26, and a species evenness index of 0.93. Based on the results of the SAC, we recommend to future researchers to make the number of transects more than 12 if conducting research in similar locations until there are no more species additions. The results of measuring abiotic factors from the three habitats have different temperatures, humidity, and wind speeds that can affect the presence of pollinating insects and flowering plants. Based on these results, the ecosystem at the research location is well-maintained, so it is still suitable as a habitat for insect pollinators.